The impact of direct and indirect mental training on students' learning of handball handling and shooting skills - Omar, L.Dr. Dakan Bakhtiar; Nouri, Prof. Dr.Araz Mohammad (Sulaimani Journal for Humanities, 2026)
This research aims to identify the impact of mental training on students' learning of handball passing and shooting skills, and to determine the differences between the two research groups in post-tests to identify the most effective teaching methods for teaching these skills. The researchers used an experimental design (two experimental groups) as it was best suited to the nature of the problem and to achieve the research results. The research sample was selected purposively from second-year students in the College of Physical Education and Sports Sciences, Department of Basic Physical Education. The research population consisted of 70 students, and a sample of 30 students was randomly selected, with 15 students in each group. These students were divided into two experimental groups: the first group received direct mental training, and the second group received indirect training. The research program lasted five weeks, with two training sessions per week. The researchers concluded that both direct and indirect mental training had a positive and effective impact on developing students' handball passing and shooting skills. Also, indirect mental training effectively affects the development of students’ handball passing and shooting skills, compared to the first experimental group. One of the most important recommendations is the necessity of using direct and indirect mental training because of their effective impact on investing time and effort in developing students’ handball passing and shooting skills.
Keywords: Direct mental training; indirect mental training; handling; shooting; handball